EBV-Induced CXCL8 Upregulation Promotes Vasculogenic Mimicry in Gastric Carcinoma via NF-κB Signaling - Zhang, Jing-yue; Du, Yu; Gong, Li-ping; Shao, Yi-ting; Wen, Jing-yun; Sun, Li-ping; He, Dan; Guo, Jin-rui; Chen, Jian-ning; Shao, Chun-kui (Frontiers in Cellular and Infection Microbiology, 2022)
Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) is a distinct entity that has conspicuously tumor microenvironment compared with EBV-negative gastric carcinoma. However, the exact role of EBV in gastric carcinogenesis remains elusive. In the present study, we found that EBV upregulated CXCL8 expression, and CXCL8 significantly promoted vasculogenic mimicry (VM) formation of gastric carcinoma cells. In accordance with these observations, CXCL8 increased cell proliferation and migration of AGS and BGC823 cells, respectively. In addition, activation of NF-κB signaling was involved in VM formation induced by CXCL8, which was blocked by NF-κB inhibitor BAY 11-7082. Furthermore, EBV encoded lncRNA RPMS1 activated the NF-κB signaling cascade, which is responsible for EBV-induced VM formation. Both xenografts and clinical samples of EBVaGC exhibit VM histologically, which are correlated with CXCL8 over-expression. Finally, CXCL8 is positively correlated with overall survival in gastric carcinoma patients. In conclusion, EBV-upregulated CXCL8 expression promotes VM formation in gastric carcinoma via NF-κB signaling and CXCL8 may serve as a novel anti-tumor target for EBVaGC.